Heuristic Algorithm for Graph Coloring Based On Maximum Independent Set - Hilal ALMARA’BEH; Amjad SULEIMAN (Journal of Applied Computer Science & Mathematics, 2012)
A number of heuristic algorithms have been developed for the graph coloring problem, but unfortunately, on any given instance, they may produce colorings that are very far from optimal. In this paper we investigated and introduce a three heuristics algorithm to color a graph based on a maximum independent set. The select a node with minimum and maximum degree consecutively (Min_Max) algorithm is implemented, tested and compared with select a node with minimum degree first (SNMD), select a node with maximum degree first (SNXD) in terms of CPU time and size of graph with different densities (0.1,0.2,…,0.9 ). The result indicated that the Min_Max algorithm and SNXD is better than SNMD based on the time of first maximum independent set, running time of CPU and the number of coloring nodes.